Analisis Pengaruh Pertumbuhan Ekonomi, SBI Dan Kurs Dollar Terhadap JII Periode Tahun 2010 Sampai 2020 - Heri Sasono; Hendra Apriwarto (CV. Ulil Albab Corp, 2022)
The purpose of this research is to test and analyze the effect of Macro Variables such as; Economic growth, Bank Indonesia Certificate (SBI) or 7-Day Reverse Repo Rate and US Dollar Exchange Rate against the Jakarta Islamic Index (JII) for the period 2010 to 2020. The number of years in the sample is 11 years, from 2010 to 2020. Multiple linear regression analysis, T test, F test, Coefficient of determination test using SPSS Version 26 software. The conclusion is that Economic Growth and SBI partially have not significant effect on JII, while the US dollar exchange rate has a significant effect on JII. But simultaneously economic growth, Bank Indonesia Certificates (SBI) and the US Dollar Exchange rate not significantly affect the Jakarta Islamic Index (JII) for the period 2010 to 2020.